Simplified Bernoulli Method to Diagnose Functional Ischemia by Coronary CTA: Comparison with SPECT - Tomizawa , Nobuo; Yamamoto , Kodai; Inoh , Shinichi; Nojo , Takeshi; Nakamura , Sunao; , (Seram, 2021)
Objective We developed a method to estimate the pressure loss across a coronary stenosis of coronary computed tomography (CT) using a simplified Bernoulli formula (estimated energy loss, EEL). The purpose of this study was to compare the diagnostic accuracy of EEL and single photon emission computed tomography (SPECT) to diagnose functional ischemia. Materials and Methods We retrospectively included 43 patients who underwent coronary CT and SPECT within 3 months followed by coronary angiography. EEL was calculated when an intermediate (40‒70%) stenosis was present using lesion length, diameter stenosis, minimal lumen area, and the myocardial volume. SPECT was performed using 99mTc-tetrofosmin with 296 MBq for stress under adenosine at 120 μg kg-1 min-1 and 740 MBq for rest studies. We compared the diagnostic performance of EEL and SPECT on a per-vessel basis to diagnose ischemia defined by fractional flow reserve (≤0.80). Results EEL and SPECT determined 29 (23%) and 20 (16%) vessels as ischemic, respectively, while 26 (21%) vessels were ischemic at catheter exam. The sensitivity and specificity was 81% and 92% for EEL and 42% and 91% for SPECT. EEL significantly improved the accuracy to diagnose ischemia than SPECT (90% vs 81%, p = 0.04). Conclusion EEL derived from coronary CT could diagnose flow limiting stenosis better than SPECT by improving the sensitivity.